Psychodrama as a new intervention for reducing fear of childbirth: a randomised controlled trial - BAYRI BİNGÖL, FADİME; DEMİRGÖZ BAL, MELTEM (My University, 2022)
This study was designed to examine the potential benefit of the addition of psychodrama classes to antenatal education as a new technique to address fear of childbirth. This was a randomised controlled trial. A total of 150 women were initially enrolled in two groups. Psychodrama sessions were added to standard antenatal education in the experiment group. The control group participated only in routine antenatal education classes. Birth outcomes and fear of childbirth were measured and analysed to assess the impact. The analysis was completed with an experimental group of 50 women and a control group of 49 women. At the conclusion of the training, it was observed that there was a greater decrease in fear of childbirth in the experiment group than in the control group. Additionally, in the postpartum period, the experimental group had a higher rate of vaginal childbirth and a shorter childbirth time than the control group. Psychodrama may be an effective means of reducing fear of childbirth and reduced caesarean section childbirth. Psychoeducation should be added antenatal education programs. Thus, it may represent an important tool in the efforts to improve maternal mental health and also provide broader social benefits.
Keywords: Sağlık Bilimleri; Hemşirelik; Health Sciences; Nursing; Klinik Tıp (MED); Klinik Tıp; HEMŞİRELİK; Clinical Medicine (MED); CLINICAL MEDICINE; NURSING; Farmakoloji (hemşirelik); Onkoloji (hemşirelik); Asistan Hemşirelik; Tıbbi ve Cerrahi Hemşirelik; Annelik ve Ebelik; LPN ve LVN; Acil Tıp Hemşireliği; Yoğun Bakım Hemşireliği; İleri ve Uzman Hemşirelik; Hemşirelik (çeşitli); Genel Hemşirelik; Pharmacology (nursing); Oncology (nursing); Nurse Assisting; Medical and Surgical Nursing; Maternity and Midwifery; LPN and LVN; Emergency Nursing; Critical Care Nursing; Advanced and Specialized Nursing; Nursing (miscellaneous); General Nursing; Antenatal education; psychodrama; psychoeducation; fear of childbirth; mode of childbirth; GROUP PSYCHOEDUCATION; NULLIPAROUS WOMEN; PREGNANT-WOMEN; W-DEQ; QUESTIONNAIRE; RELAXATION; ANXIETY; SUPPORT; VERSION; RISK; Antenatal education; psychodrama; psychoeducation; fear of childbirth; mode of childbirth